1980
DOI: 10.1007/bf00912859
|View full text |Cite
|
Sign up to set email alerts
|

The selection of paraprofessional telephone counselors using the California psychological inventory

Abstract: Comparing groups of 36 veteran telephone counselors with 36 matched age and sex control subjects on the CPI revealed substantial differences on a number of scales. Subsequent development of weighted formulae via regression analysis led to very accurate predictions as to which individuals were telephone counselors or controls. Various cutoff scores and their uses are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…First, while in many of the studies, personality measures were administered to subjects at the beginning of their volunteer work, in others this was done at some time after they had begun their volunteer duties (Howarth, 1976;Jamison and Johnson, 1975;King et al, 1980;Smith and Nelson, 1975;Strickland, 1965;Tapp andSpanier, 1973, Turner, 1973). First, while in many of the studies, personality measures were administered to subjects at the beginning of their volunteer work, in others this was done at some time after they had begun their volunteer duties (Howarth, 1976;Jamison and Johnson, 1975;King et al, 1980;Smith and Nelson, 1975;Strickland, 1965;Tapp andSpanier, 1973, Turner, 1973).…”
Section: Methodological Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…First, while in many of the studies, personality measures were administered to subjects at the beginning of their volunteer work, in others this was done at some time after they had begun their volunteer duties (Howarth, 1976;Jamison and Johnson, 1975;King et al, 1980;Smith and Nelson, 1975;Strickland, 1965;Tapp andSpanier, 1973, Turner, 1973). First, while in many of the studies, personality measures were administered to subjects at the beginning of their volunteer work, in others this was done at some time after they had begun their volunteer duties (Howarth, 1976;Jamison and Johnson, 1975;King et al, 1980;Smith and Nelson, 1975;Strickland, 1965;Tapp andSpanier, 1973, Turner, 1973).…”
Section: Methodological Issuesmentioning
confidence: 99%
“…Hersch, Kulik, and Scheibe (1969) and King et al (1980), for example, report that volunteers are more flexible, more oriented toward independent achievement and more tolerant than non-volunteers. Tapp and Spanier (1973) found that these individuals possess more self-actualizing values than non-volunteers, while Howarth (1976) found them to be less anxious.…”
Section: Emotional Stabilitymentioning
confidence: 99%
“…A self-selection of persons working voluntarily for crisis support services might also explain the stigma differences between the counselor sample and the general population sample. Previous research demonstrated differences in personality characteristics between crisis hotline volunteers and non-volunteers in empathy factors and agreeableness (sample of students [42]), in tolerance and psychological mindedness (crisis hotline counselors vs. matched control [43]) and differences in prosocial motivation explained by interpersonal values like harmony and helpful influence (sample of TES volunteers compared to matched nonclinical reference sample [44]). It is also conceivable that a combination of both - self-selection as well as the engagement for the TES - explain differences in the two samples and in depression stigma scores.…”
Section: Discussionmentioning
confidence: 99%
“…Most often, the focus of their research has been to identify personality correlates of graduate school and postgraduate professional success (e.g., Tinsley & Tinsley, 1977). Personality inventories, particularly the California Personality Inventory (CPI; Gough, 1987), have been used in a variety of other fields to predict training and vocational outcomes (e.g., Flom, 1974;King, McGowen, Dornan, & Schweibert, 1980; Mills & Bohannon, 1980;Mufson, 1986). Such studies have not been done with school psychologists, however.This study is a first step in examining the personality characteristics of school psychologists.…”
mentioning
confidence: 99%